Model for determining the efficiency of operation of modularly distributed systems of aircraft considering cost factors and uncertainty factors - ALEKSEEVICH, GORELOV BORIS; ANATOLYEVNA, BURDINA ANNA; DMITRIEVICH, DAVYDOV ALEXEY; NIKOLAEVNA, KALOSHINA MARINA; VIKTOROVNA, BONDARENKO ANNA (The journal of contemporary issues in business and government, 2021)
The study examines modularly distributed systems using the example of unmanned aerial vehicles (UAVs). It is determined that UAVs are divided into three main classes: strategic, tactical and special purpose. The concept of the efficiency of operation of modularly distributed systems of aviation technology is introduced, considering the factors of uncertainty and cost. In comparison with the manned aircraft, there are emphasized the properties and advantages of the UAV. The scenario of joint use of UAVs has been substantiated. A model is being developed for determining the required number of UAVs in a group based on preliminary information regarding the tactical situation in the group’s area of operations; the estimated number and nature of targets located in the target area and other parameters. A probabilistic model for analyzing the effectiveness of the actions of a group of modularly distributed systems of aircraft, considering the cost factors and uncertainty in extinguishing forest fires, is proposed.